KOMUNIKASI EFEKTIF SEBAGAI KUNCI EDUKASI POLA HIDUP SEHAT PENDERITA DIABETES - Sudarsih, Sri; Santoso, Windu; Taqiuddin, Muhammad Hafidh (Universitas Mataram, 2025)
Diabetes mellitus, commonly known as diabetes, is a dangerous health problem and is prevalent in Indonesia. The prevalence of diabetes in Indonesia is increasing, necessitating early treatment, one of which is through the adoption of a healthy lifestyle. Diabetes must be treated as early as possible to avoid more serious consequences later in life. Educating the public about the importance of a healthy lifestyle, especially for groups at high risk of developing diabetes, is crucial. The goal of this community service activity is to educate people with diabetes about healthy lifestyles through effective communication. The educational activity for healthy lifestyles for diabetes sufferers uses the Participatory Action Research (PAR) approach. Education is carried out by a team for families of diabetes sufferers. The implementation of the activity consists of 2 stages: the preparation stage and the implementation stage. Measurement of the level of knowledge of participants related to the educational material is carried out before and after the education. Based on the activities that have been carried out by the community service team, the following results were obtained: the implementation of education was carried out by implementing the stages in therapeutic communication. This community service activity is an implementation of effective communication through education that runs according to plan and the evaluation results show the implementation of effective communication when education has used the stages in therapeutic communication consisting of the pre-interaction stage, the orientation stage, the work stage and the termination stage. The results of measuring participant knowledge using a questionnaire showed that 100% of knowledge about healthy lifestyles for diabetes sufferers increased, namely in the good and sufficient categories. There is a need for improvement in effective communication skills so that the implementation of the stages in therapeutic communication can be implemented better and the educational objectives can be achieved.